Online Genetic-Fuzzy Forward Controller for a Robot Arm - Ali, Prof Dr. Abduladeem A.; Kudaer, Amal J. (Iraqi Journal for Electrical and Electronic Engineering, 2009)
The robot is a repeated task plant. The control of such a plant under parameter variations and load disturbances is one of the important problems. The aim of this work is to design Genetic-Fuzzy controller suitable for online applications to control single link rigid robot arm plant. The genetic-fuzzy online controller (forward controller) contains two parts, an identifier part and model reference controller part. The identification is based on forward identification technique. The proposed controller it tested in normal and load disturbance conditions.